Synthesis of ethers containing 1,3-dioxolane and gem-dichlorocyclopropane fragments - Sh. Sh. Dzhumaev; Yu. G. Borisova; G. Z. Raskil’dina; U. Sh. Kuzmina; R. R. Daminev; S. S. Zlotskii (Тонкие химические технологии, 2021)
Objectives. This study aimed to obtain ethers containing gem-dichlorocyclopropane and 1,3-dioxolane fragments and evaluate their cytotoxic properties against HEK293, SH-SY5Y, MCF-7, and A549 cell lines.Methods. The qualitative and quantitative compositions of the reaction masses were determined using mass spectrometry (using a Chromatek-Kristall 5000M device with the 2012 National Institute of Standards and Technology, USA database) and nuclear magnetic resonance spectroscopy (using a Bruker AM-500 device with operating frequencies of 500 and 125 MHz).Results. Ethers containing gem-dichlorocyclopropane and 1,3-dioxolane fragments were synthesized in the presence of a catamine AB catalyst. The structures of the obtained substances were confirmed using gas-liquid chromatography, mass spectrometry, and nuclear magnetic resonance spectroscopy. The cytotoxicity of the esters was studied against HEK293, SH-SY5Y, MCF-7, and A549 cell lines.Conclusions. Ethers containing gem-dichlorocyclopropane and 1,3-dioxolane fragments were obtained in quantitative yields; however, only 4-{[(2,2-dichloro-3-{[(2,2-dichlorocyclopropyl) methoxy]methyl}cyclopropyl)methoxy]methyl}-2,2-dimethyl-1,3-dioxolane exhibited cytotoxic activity against HEK293, SH-SY5Y, MCF-7, and A549 cell lines.